Flexible bronchoscopy - Wang, Ko Pen; Mehta, Atul C.; Turner, J. Francis, Jr. (Hoboken, NJ : John Wiley & Sons, 2020)
"With the development of new instruments and the refining of new techniques, flexible bronchoscopy has become one of the most frequently performed invasive procedures in pulmonary medicine. This fourth edition of Flexible Bronchoscopy is an essential addition to the bronchoscopist's bookshelf, with four new chapters and fully updated content. It highlights possible complications, contra-indications and precautions. In addition it addresses all current techniques and future technologies in interventional bronchoscopy. For ease of use Flexible Bronchoscopy is divided into four major sections: Fundamentals of Bronchoscopy, Diagnostic Bronchoscopy, Therapeutic Bronchoscopy, Special Considerations. Flexible Bronchoscopy is an ideal training manual for all respiratory and pulmonary physicians, as well as trainees and residents working in the field of respiratory medicine, who need to develop the skill of interventional bronchoscopy"--
A Short History of Flexible Bronchoscopy / HD Becker -- Professor Ikeda's Genius -- The Flexible Bronchoscope & Flexible Bronchoscopy Training / Akulian J, Feller-Kopman D -- Applied Anatomy & Physiology of the Airways / Atul C. Mehta, and J. Francis Turner Jr. -- Infection Control and Radiation Safety in the Bronchoscopy Suite / Jain P, Mehta AC -- Anesthesia for Bronchoscopy / Moore BA, Turner JF, Wang KP -- Indications and Contraindications in Flexible Bronchoscopy / Robert F. Browning Jr, J. Francis Turner Jr, Ko-Pen Wang -- Radial-Probe Ultrasonography in Flexible Bronchoscopy / Kurimoto N, Isobe T, Inoue T, Miyazawa T -- Linear-Probe Ultrasonography in Flexible Bronchoscopy / Pattison A, Yasufuku K -- Early Diagnosis of Lung Cancer : Autofluorescence Bronchoscopy, Narrowband Imaging, Optical Coherence Tomography, Elastography / Meyers R, Lam S -- Electromagnetic Navigation Bronchoscopy / Leon CA, Gildea TR -- Virtual Bronchoscopic Navigation / Baveja S, Hohenforst-Schmidt W, Turner JF, Wang KP -- Indirect Laryngoscopy: Anatomy and Use of the Flexible Bronchoscope / Carlson E, Schlieve T -- Bronchoscopy for Airway Lesions : Washing, Brushing and Endobronchial Biopsy / HD Becker -- Bronchoalveolar Lavage / Wei Z, Huang Y, Helmers R -- Bronchoscopic Lung Biopsy / McKayS, BrowningRF, TurnerJF, Wang KP -- Transbronchial needle aspiration for cytology and histology specimens / Xia Y, Turner JF, Mehta AC, Wang KP -- Staging of Bronchogenic Carcinoma : Our Path from 1994 to now. / JF Turner, Ko-Pen Wang -- The Future of Interventional Pulmonology / Sagar AE, Ost D -- Application of Laser, Electrocautery, Argon Plasma Coagulation, Radiofrequency Ablation, and Cryotherapy in Flexible Bronchoscopy / Khemasuwan D, Bilaceroglu S -- Endobronchial Brachytherapy, Placement of Fiducial Markers, Radiofrequency Ablation and Microwave Therapy / Michael A. Jantz -- Foreign Body Removal and Flexible Bronchoscopy / Folch EE, RabinAS -- The Role of Bronchoscopy in Hemoptysis / Zhou GW, Huang H, Bai C, Patel SR -- Endobronchial Stents / Murgu SD, Kurman JS, Turner JF, Mehta AC, Wang KP -- Balloon Bronchoplasty / Bevill B, Paoletti L, Pastis N -- Rigid Bronchoscopy / J. Francis Turner Jr and Ko-Pen Wang -- Pediatric Flexible Fiberoptic Bronchoscopy / Liu X, Meng C, Ma J, Zhao S -- Bronchoscopy in the Intensive Care Unit / Sadoughi A, Chen A -- Endoscopic Management of Asthma / Chrissian AA, Makani S, Simoff M -- Endoscopic Management of Emphysema / Gasparini S, Bonifazi M -- Endoscopic Management of Bronchopleural Fistulas / Ming-yao K, Huang H, Turner JF -- Clinical Management of Benign Airway Stenosis and Tracheobronchomalacia / Xia Y, Li Q
BIBINDX
Keywords: Bronchoscopy; Bronchoscopy; Bronchial Diseases -- diagnosis; Bronchial Diseases -- therapy; Electronic books